Constitution of mucosa‐associated microbiota in the lower digestive tract does not change in early stage of non‐alcoholic fatty liver disease with fecal dysbiosis. Issue 10 (29th August 2022) - Asaji, Naoki; Inoue, Jun; Hayashi, Hiroki; Tokunaga, Eri; Shimamoto, Yusaku; Kinoshita, Masato; Tanaka, Takeshi; Sakai, Arata; Yano, Yoshihiko; Ueda, Yoshihide; Kodama, Yuzo
Abstract: Background and Aim: Regarding the gut–liver axis, fecal dysbiosis is implicated in the pathogenesis of non‐alcoholic fatty liver disease (NAFLD). The significance of mucosa‐associated microbiota (MAM, which is present in the mucin layer covering the intestinal mucosa) has not been well explored. We aimed to clarify the characteristics of MAM in patients with NAFLD. Methods: MAM were obtained from seven patients with early‐stage NAFLD and seven controls by colonoscopy in five locations (terminal ileum, cecum, ascending and sigmoid colon, and rectum) using mucosal brushes. The microbial 16S rDNA profiles of the MAM and fecal microbiota of patients in the NAFLD and control groups were analyzed. Results: α‐diversities of fecal microbiota were decreased in patients with NAFLD (observed species, Shannon index, and Chao1: 174.57 vs 134.86, 5.51 vs 4.65, and 206.34 vs 167.91; P  = 0.048, 0.067, and 0.087, respectively), and microbial composition analyses by principal coordinate analysis differed between the fecal microbiota of patients with NAFLD and those of controls (permutational analysis of variance [PERMANOVA] of weighted and unweighted: Pseud‐ F : 1.4179/ P ‐value: 0.05 and Pseud‐ F : 2.1497/ P ‐value: 0.049, respectively). However, α‐diversities or microbial composition of MAM in most parts of the intestine did not differ significantly between the NAFLD and control groups. Unclassified Rikenellaceae, Oscillospira, Odoribacter, unclassified clostridiales, and Holdemania were decreased in the feces of patients with NAFLD (determined by linear discriminant analysis effect size), but five (except Holdemania ) of the six genera were not decreased in the MAM of these patients. Conclusion: In early‐stage NAFLD, MAM was uniform and relatively stable throughout the intestine, even when fecal dysbiosis appeared. Abstract : The α‐diversities of fecal microbiota were decreased in patients with non‐alcoholic fatty liver disease (NAFLD), and microbial composition by principal coordinate analysis differed between the fecal microbiota of patients with NAFLD and those of controls. However, α‐diversities or microbial composition of mucosa‐associated microbiota (MAM) in most parts of the lower gut (from the terminal ileum to the rectum) did not differ between the NAFLD and control groups. In early‐stage NAFLD, MAM was uniform and relatively stable throughout the intestine, even when fecal dysbiosis appeared.